Development of the P5 Module for Hydroponic Pakcoy Cultivation Based on Bioentrepreneurship in Developing Students' Independence Character and Science Process Skills - Shinta Yunitasari; Aloysius Handoko; Akhmad; Usman; Evi Palenewen; Elsje Theodora Maasawet (Jurnal Penelitian Pendidikan IPA, 2025)
This study aimed to develop a Strengthening Pancasila Student Profile (P5) module on hydroponic pakcoy cultivation based on bioentrepreneurship as a learning medium to foster independence and scientific skills among eighth-grade students at SMP Negeri 4 Loa Janan. The research employed a Research and Development (R&D) design following the ADDIE model, which consists of the stages of Analysis, Design, Development, Implementation, and Evaluation. Data were collected through observations, expert validation questionnaires, and limited student trials. The results indicated that the developed module was highly feasible, as evidenced by expert validation scores from material experts, media experts, and practitioners, all categorized as “very good.” The implementation results showed that the module effectively enhanced students’ independence through hydroponic cultivation activities and improved their scientific skills through observation, experimentation, and plant growth analysis. The integration of bioentrepreneurship elements provided meaningful and contextual learning experiences that connected science with real-world entrepreneurial opportunities. In conclusion, the bioentrepreneurship-based P5 module was effective and feasible as a learning medium to strengthen students’ academic competence, independence, and 21st-century skills.